PENGARUH ORIENTASI PASAR, INOVASI PRODUK, DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA PERUSAHAAN - Kandrio Kandrio; Hasanuddin Bua; Patwayati Patwayati (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The objectives of the study are 1.) To examine and analyze the effect of market orientation on marketing performance. 2.) To examine and analyze the influence of entrepreneurship orientation on marketing performance. 3.) To examine and analyze the effect of product innovation on marketing performance. 4.) To examine and analyze market orientation, product innovation and entrepreneurship orientation towards marketing performance. The method used in sampling was the census method, which is all of the cashew industries in Kendari. Data collection was carried out by distributing questionnaires. The researcher set the sample with the total population of 30 people. The resercher used SPSS 20 for Windows to support existing primary data. The result of the study indicates that: (1) Market orientation has positive and significant effects on marketing performance. (2). Product innovation has positive and significant effects on marketing performance. (3) Entrepreneurial orientation has positive and significant effects on marketing performance. (4). Market orientation, product innovation and entrepreneurship orientation have positive and significant effects on marketing performance. For further research, researcher suggests using other variables, such as competitive advantage variable and product quality.Keywords: market orientation, product innovation, entrepreneurship orientation, and market performance